Screening for antibacterial activity of Andrographis paniculata used in Malaysian folkloric medicine: a possible alternative for the treatment of skin infections - Sule, Abubakar; Ahmed, Qamar Uddin; Abd. Samah, Othman; Omar, Muhammad Nor (Southern Illinois University Carbondale, USA., 2010)
In this study non-polar (dichloromethane) and polar (MeOH & aqueous) extracts of A. paniculata (whole plant) were evaluated for in vitro antibacterial activity against 12 skin disease causing bacterial strains (7 gram positive strains; Staphylococcus saprophyticus, Staphylococcus epidermis, Staphylococcus aureus, Streptococcus pyogenes, Bacillus anthracis, Micrococcus luteus, Enterococcus faecalis) and 5 gram negative strains; Proteus mirabilis, Proteus vulgaris, Klebsiella pneumoniae, Neisseria meningitis, Pseudomonas aeruginosa ) using the disc diffusion method at three concentrations; 1000, 500, and 250 µg/disc respectively in order to ascertain its folkloric claim to treat skin infections. The extracts showed significant antibacterial activities against both the Gram-positive and Gram-negative bacterial strains tested. Highest significant antibacterial activity was exerted by the MeOH extract against E. faecalis at 1000 µg/disc (24.00 ± 0.00 mm) and the least activity by the DCM extract against N. meningitis at 250 µg/disc (6.00 ± 0.00mm). The minimum inhibitory concentration ranged between 150 µg /mL and 300 µg /mL depending on microorganism and various extracts. Presence of phytochemicals such as terpenoids, tannins, flavonoids, saponins, alkaloids, amino acids and steroids were observed. These results candidly suggest the presence of promising antibacterial substances in the polar as well as non-polar extracts which could be potential phytomedicine for the treatment of skin infections caused by pathogenic bacterial strains. These findings explicitly support its traditional claims and form a strong basis for further efforts to explore A. paniculata’s antibacterial potential to treat skin frailties efficaciously. Our results confer the utility of this plant extracts in developing a novel broad spectrum antimicrobial agent.